2020
DOI: 10.3390/app10165702
|View full text |Cite
|
Sign up to set email alerts
|

Modern Aspects of Cyber-Security Training and Continuous Adaptation of Programmes to Trainees

Abstract: Nowadays, more-and-more cyber-security training is emerging as an essential process for the lifelong personnel education in organizations, especially for those which operate critical infrastructures. This is due to security breaches on popular services that become publicly known and raise people’s security awareness. Except from large organizations, small-to-medium enterprises and individuals need to keep their knowledge on the related topics up-to-date as a means to protect their business operation or to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Pattinson et al [58] put forth a concept framework of information security training considering individual differences of learning preferences. Hatzivasilis et al [59] developed an adoptable training program and a pilot system about cyber-security considering trainee type, trainee's needs and his/her performance. Our findings have implications for institutes and organizations as they can help to develop personalized training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Pattinson et al [58] put forth a concept framework of information security training considering individual differences of learning preferences. Hatzivasilis et al [59] developed an adoptable training program and a pilot system about cyber-security considering trainee type, trainee's needs and his/her performance. Our findings have implications for institutes and organizations as they can help to develop personalized training programs.…”
Section: Discussionmentioning
confidence: 99%
“…The theory is rarely utilised to explain what factors are affecting users' compliance with security policies or even provide empirical evidence from their actual application. In general, it is suggested that training programmes should make use of methods and contents that are actively engaging trainees and motivate them to undergo systematic cognitive processing of the taught information [17,20]. Apart from modern technological tools (e.g., simulation, serious games), the continuous communication of the trainer with the learners is vital to improving users' security compliance [12,17,20].…”
Section: Adopting Training In the Workplacementioning
confidence: 99%
“…Researches for security training ordinarily incorporate pedagogical principles as the primary methodology to enhance the user's compliance [18,20,21]. In 1998, Baldwin and Ford [22] defined the transfer of learning to the working environment as "the degree to which trainees effectively apply the knowledge, skills, and attitudes gained in the training context to the job".…”
Section: Adopting Training In the Workplacementioning
confidence: 99%
See 2 more Smart Citations